2019
DOI: 10.1590/1089-6891v20e-47449
|View full text |Cite
|
Sign up to set email alerts
|

DIARRHEAGENIC Escherichia coli IN RAW MILK, WATER, AND CATTLE FECES IN NON-TECHNIFIED DAIRY FARMS

Abstract: This study focused on detecting diarrheagenic Escherichia coli, enteropathogenic E. coli (EPEC), Shiga-toxin-producing E. coli (STEC), enterohemorrhagic E. coli (EHEC or STEC:EPEC), enterotoxigenic E. coli (ETEC), and enteroaggregative E. coli (EAEC) in raw milk, water, and cattle feces sampled from non-technified dairy farms located in the northeastern São Paulo State, Brazil. Thirty-six water samples were collected at different points, namely, water wells (8 samples), water intended for human consumption (8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
15
1
1
Order By: Relevance
“…Nesse sistema, o leite cru, armazenado em tanque de expansão a 4 ºC por até 48 horas e transportado para a indústria beneficiadora em tanques isotérmicos (BRASIL, 2015;BRASIL, 2018a;2018b). Esse processo visa reduzir o desenvolvimento da microbiota mesofílica, dentre as quais o gênero Staphylococcus spp., que se destaca como micro-organismo patogênico, potencialmente reconhecido como produtor de toxinas (RIBEIRO et al, 2019;PICOLI et al, 2014;MATTOS et al, 2010).…”
Section: Discussionunclassified
“…Nesse sistema, o leite cru, armazenado em tanque de expansão a 4 ºC por até 48 horas e transportado para a indústria beneficiadora em tanques isotérmicos (BRASIL, 2015;BRASIL, 2018a;2018b). Esse processo visa reduzir o desenvolvimento da microbiota mesofílica, dentre as quais o gênero Staphylococcus spp., que se destaca como micro-organismo patogênico, potencialmente reconhecido como produtor de toxinas (RIBEIRO et al, 2019;PICOLI et al, 2014;MATTOS et al, 2010).…”
Section: Discussionunclassified
“…The presence of a high number of coliforms in the cheese-making water may cause some defects in the food product, such as early blowing defect, which results in the presence of small holes in the cheese. The high incidence of these microorganisms in water is mainly due to environmental contamination or inefficient chlorination (FAROOQ et al, 2008;TRMČIĆ et al, 2016) and it is important to guarantee the quality of water to avoid contamination of milk and cheese (RIBEIRO et al, 2019). However, according to Saraiva et al (2012), just over half of the producers demonstrated some control over water use, such as chlorination control or periodic physicochemical and microbiological analyses..…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic Escherichia coli can be detected in raw milk (RIBEIRO et al, 2019). E. coli presence in raw milk cheese may indicate a milk contamination of fecal origin or mammary infections (CONTANZO et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations